Istanbul hotels from a 360 0 perspective: A comprehensive view of the Istanbul accommodation industry - Maria D. Alvarez; Burçin Hatipoğlu; Kıvanç İnelmen; Dilek Ünalan (PASOS Revista de Turismo y Patrimonio Cultural, 2012)
As destinations are striving to become more competitive and attract visitors and tourists, the performance of its enterprises, including hotels is essential. Despite the significance of research in this area, to date, there are no studies that analyze the accommodation industry of a given destination from a broad perspective, since most of the investigations focus on a specific area of the organization and its relationship with the hotel’s performance. Therefore, the research aims to provide a comprehensive view of the accommodation industry in Istanbul. Moreover, the study will also attempt to establish a standard data collection instrument that can be used in the future as a benchmarking tool. The research will be carried out on a number of complementary perspectives that include management practices, financial performance measures, operational indicators, employee profile and attitudes, customer profile and satisfaction, environmental practices and use and investment in technology. Furthermore, the study attempts to determine the most important factors that affect the performance of the hotels and to explore the relationship between the different variables included.